Підготовка вчителів англійської мови у вищих навчальних закладах Китайської народної республіки - Тішкова, Олена Федорівна (НУБіП України, 2019)
Дисертація на здобуття наукового ступеня кандидата педагогічних наук зі спеціальності 13.00.04 «Теорія і методика професійної освіти». Національний університет біоресурсів і природокористування України. Київ, 2019. У дисертації здійснено теоретичне та практичне дослідження особливостей підготовки майбутніх учителів англійської мови у Китайській Народній Республіці.На основі аналізу праць китайських і зарубіжних дослідників щодо проблеми підготовки вчителів англійської мови у Китайській Народній Республіці визначено тенденції і шляхи її реформування, а саме: перехід від формування мовної компетентності до формування комунікативної компетентності, запровадження комунікативного вивчення англійської мови у процес підготовки майбутніх учителів відповідного профілю, здійснення підготовки зазначених фахівців за подвійними програмами. З’ясовано, що найефективнішим засобом мотивації китайських студентів до вивчення англійської мови є необхідність складання стандартизованих екзаменів різного рівня (національного, регіонального (провінційного), місцевого). З’ясовано основні програмні вимоги й методи, які використовуються у навчальному процесі щодо підготовки вчителів англійської мови у Китайській Народній Республіці. Встановлено подібності та розбіжності у підготовці вчителів англійської мови у вищих навчальних закладах Китайської Народної Республіки й України. На основі порівняльного аналізу професійної підготовки вчителів англійської мови в університетах Китайської Народної Республіки і України сформульовано рекомендації щодо використання деяких аспектів досвіду китайських університетів, зокрема: запровадження моделі «глобальної англійської мови» (Global English model) з акцентом на комунікативну та діяльнісну компетентність; обов’язкове складання студентами стандартизованих тестів; перегляд співвідношення обов’язкових і вибіркових дисциплін; регламентування обсягу вокабуляру для оволодіння студентами у межах різних програм навчання; запровадження обов’язкового єдиного екзамену з англійської мови після завершення студентами курсу її вивчення
Thesis for a Candidate Degree in Pedagogical Sciences, specialty 13.00.04 «Theory and Methodology of Professional Education». National University of Life and Environmental Sciences of Ukraine. Kyiv, 2019. The dissertation deals with theoretical and practical study of the peculiarities of future English language teachers training in the People's Republic of China. Based on the analysis of the works of Chinese and foreign researchers on the problem of English language teacher training in the People's Republic of China, the tendencies and ways of its reforming have been determined, namely: transition from language competence formation to communicative competence formation, introduction of communicative English language learning in the training process of future teachers of corresponding profile, training of these specialists in double degree programs. It is noted that the current process of reforming English language teaching in China's higher education is a reflection of the need for change in response to the growing role of English in the globalization process. In doing so, the priority in teaching English at Chinese universities is the Global English model, with an emphasis on communicative and activity competence to meet the new requirements of global communication. An empirical study, which was carried out regarding the studying status of future English teachers at Chinese universities has provided a basis for determining the level of motivation and orientation of students for the professional activities of English teachers. It has been found that the most effective way to motivate Chinese students to learn English is to take standardized exams at different levels (national, regional (provincial), local). Quantitative indicators of students' orientation to the English language teacher's profession fluctuate depending on the course (62 % in the first year, about 50 % in the third year and there is an unanimous desire to work as a teacher in the fifth year – 93 %). The basic program requirements and methods that are used in the educational process for the preparation of English teachers in the People's Republic of China have been clarified. The purpose of the current national English language teacher training program is to develop in them the ability to communicate information in the target language; the main tasks are to develop skills in reading at a high level, and in listening, speaking, writing and translation at a fairly good level; English language teaching methodology involves the use of learner-centered methods and the combination of grammar-translation method with the audio-visual method; the vocabulary that a student should know (6500 words) is regulated. Similarities and differences were found in the preparation of English language teachers at higher education institutions in the People's Republic of China and Ukraine. Similar features include, but are not limited to: increasing popularity of English among students; increasing the attention of the state to the spread of English language learning in schools and therefore the requirements for the proper quality of the English language teacher training process; dominance of audio-visual method in English language teacher training in both countries until recently. The main differences are in the following aspects: stronger influence of national cultural traditions, in particular Confucianism, on the system of teaching English in the People's Republic of China; predominancy of external motivation among Chinese students to choose a profession of English teacher; increasing the desire for innovation in the preparation of English language teachers in Ukraine. Based on a comparative analysis of the professional training of English teachers at the universities of the People's Republic of China and Ukraine, recommendations have been formulated on the use of some aspects of Chinese universities' experience, namely: introduction of the Global English model with an emphasis on communicative and activity competence; it is compulsory for students to take standardized tests; reviewing the correlation between compulsory and elective disciplines, modeled on the Chinese «3+1 program», when students are studying three compulsory and one elective disciplines at will; structuring the content of the English language teacher training in three consecutive blocks, which envisage first studying basic disciplines, then disciplines of professional training and lastly the narrow professional disciplines and passing pedagogical practice; transition to the formation of communicative competence; analysis of the possibility of extending the training of future English language philologists at double degree programs; regulating the amount of vocabulary for students’ mastering within the framework of various training programs; introduction of a compulsory unified English exam after students complete the course; to optimize the practical training of English teachers by agreeing on the passive and active part of the practice and introducing practices of different duration in each course. The study does not cover the whole problem of professional training of English language teachers. Further research will require such aspects as: features of the organization of practices and internships of future English teachers, differentiation of their training programs, search for a means of motivating school graduates to choose the profession of English teacher and entry to study in the relevant specialty
Keywords: професійна підготовка; навчальна програма; зміст; методика; мотивація; вчитель англійської мови; professional training; curriculum; content; methodology